Mass Equidistribution for Saito-Kurokawa Lifts - Jääsaari, Jesse; Lester, Stephen; Saha, Abhishek (Springer Nature, 2025)
Let F be a holomorphic cuspidal Hecke eigenform for of weight k that is a Saito–Kurokawa lift. Assuming the Generalized Riemann Hypothesis (GRH), we prove that the mass of F equidistributes on the Siegel modular variety as k⟶∞. As a corollary, we show under GRH that the zero divisors of Saito–Kurokawa lifts equidistribute as their weights tend to infinity.